Low pressure plasma spraying of sol-gel Al2O3/SiC nanocomposite coatings - Jiansirisomboon, S; Roberts, S; Grant, P (2001)
This paper describes the manufacture of a new ceramic coating system based on Al2O3/SiC nanocomposite powder prepared by sol-gel processing followed by low pressure plasma spraying (LPPS) onto stainless steel substrates. In order to produce nanocomposite coatings of good adhesion and low porosity, the substrates were water-cooled to minimise thermal stresses associated with coefficient of thermal expansion mismatch and a CoNiCrAlY bond coat was used. The sol-gel powder feedstock and the as-sprayed coatings have been characterised by a combination of scanning electron microscopy (SEM), transmission electron microscopy (TEM), x-ray diffraction (XRD), and Nuclear Magnetic Resonance (NMR). The coating characteristics were compared with a reference Al2O3 coating prepared from commercial feedstock powder. The thermal exposure of the sol-gel powder during spraying caused phase-changes and phase-decomposition. Examination of the sprayed coatings showed that it was possible to maintain the 20-200 nm SiC particles in the final Al2O3/SiC nanocomposite coating. The coatings also contained both stable alpha-Al2O3 and metastable gamma-Al2O3. Some minority phases such as silica and aluminosilicate formed in the sol-gel feedstock powder were fully decomposed during LPPS. This preliminary study indicates that sol-gel and LPPS processing is a potential route for the manufacture of nanocomposite coatings, which may offer significant improvements in some aspects of coating properties.